Desarrollo e implementación de una solución de inteligencia de negocios para la toma de decisiones de cobrabilidad y morosidad a nivel gerencial en Electro Oriente S.A. - 2020 - Navarro Pereyra, Victor Gabriel (2021)
The Commercial Management, in coordination with the General Management of the company Electro Oriente Sociedad Anónima, is in charge of controlling, based on results, the invoicing, collection, delinquency related to the company's clients. The management is faced with the inconvenience of having unreliable information from the commercial system due to its disorganization and raw, which does not allow to have in real time the billing information, the collection rates and delinquency of the company, and also does not generate the necessary number of reports that are required to make decisions regarding contingency plans to improve them. Faced with this fact, the question was raised, in what way will the development and implementation of a Business Intelligence Solution contribute to Decision Making with respect to the collection and delinquency rates of ELOR S.A. - 2020? The objective was to determine the contribution of this solution and as such, the hypothesis was that an improvement in Decision Making is expected. The study was quantitative, applied, with a non-experimental, analytical, longitudinal, prospective intervention; With a longitudinal trend design, with pre and post test, the population consisted of 124 Decision Making, 59 before implementation and 65 with the Business Intelligence Solution. For data processing, SPSS version 22 was used. To compare the time to generate a report, Mann-Whitney U was applied, and to compare the necessary number and the reliability of the reports, Chi square of homogeneity was applied with a level of 5% significance. The conclusion regarding the question, objective and hypothesis is that the development and implementation of a Business Intelligence Solution will improve Decision Making regarding the collection and delinquency rates of ELOR S.A. - 2020.